2020
DOI: 10.1021/acs.jpclett.0c03267
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Energy- and Electron-Transfer Dynamics in Photoexcited Mn-Doped CsPbBr3 Perovskite Nanoplatelet Architecture

Abstract: Mn-doped perovskites have already been widely explored in the context of interesting optical, electronic, and magnetic properties. Such fascinating traits showcased by them explain the huge augmentation in the device efficiency, directing their widespread application in the field of solar cells, energyharvesting sectors, and light-emitting diodes. However, the underlying photophysics governing the overall charge carrier dynamics in Mn-doped CsPbBr 3 nanoplatelets (NPLs) has never been discussed and therefore d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
2
21
2
Order By: Relevance
“…The presence of Mn 3+ in perovskite samples was also invoked to rationalize the ferromagnetic coupling in MAPb 1– x Mn x I 3 , proposed to arise from Mn 2+ –I – –Mn 3+ motifs . Very recently, Babu et al revealed the formation of a transient charge-transfer state in Mn:CsPbBr 3 , suggesting that a spin-allowed charge-transfer process (concurrent to energy transfer) related to Mn 3+ formation is likely to occur …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of Mn 3+ in perovskite samples was also invoked to rationalize the ferromagnetic coupling in MAPb 1– x Mn x I 3 , proposed to arise from Mn 2+ –I – –Mn 3+ motifs . Very recently, Babu et al revealed the formation of a transient charge-transfer state in Mn:CsPbBr 3 , suggesting that a spin-allowed charge-transfer process (concurrent to energy transfer) related to Mn 3+ formation is likely to occur …”
mentioning
confidence: 97%
“… 48 Very recently, Babu et al revealed the formation of a transient charge-transfer state in Mn:CsPbBr 3 , suggesting that a spin-allowed charge-transfer process (concurrent to energy transfer) related to Mn 3+ formation is likely to occur. 49 …”
mentioning
confidence: 99%
“…Moreover, there is an onset of a new negative feature (bleach) in the lower-energy region around 412–430 nm for Eu-CsPbCl 3 . Such a bleach could be attributed to either a formation of an intermediate charge transfer band or the presence of defect states. , …”
mentioning
confidence: 99%
“…As reported, the energy-transfer process in the doped system is related with the decrement of the excitonic decay in host emission with the increase in the emission of dopants, leading to a decrease in the PL decay lifetime of the excitonic emission in doped materials in comparison with that of undoped samples. 35,42 In our case, undoped CsPbCl 3 NCs are very difficult to collect in the absence of Mn 2+ ions, and thus we did not compare the lifetime between doped and undoped samples. The PL decay plots of representative Mn 2+ -doped CsPbCl 3 NCs monitored at 400 nm and 600 nm are provided in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The unique optical properties of Mn-doped LHP NCs and their promising applications led to worldwide research on various synthetic protocols. 38–44 Wang et al synthesized cube-like Mn 2+ -doped CsPbCl 3 NCs by using a hot-injection procedure. 45 Zheng and coworkers achieved very high Mn 2+ dopant substitution in Mn-doped 2-dimensional CsPbCl 3 nanoplatelets using a postsynthetic solvothermal procedure.…”
Section: Introductionmentioning
confidence: 99%